Electrospun three-layered polymer nanofiber-based porous carbon nanotubes for high-capacity energy storage. Issue 1 (23rd December 2016) - Lee, Jun Seop; Jun, Jaemoon; Cho, Sunghun; Kim, Wooyoung; Jang, Jyongsik
Abstract : Highly porous carbon nanotubes are synthesized using dual-nozzle co-electrospinning of three polymer solutions and following heat treatment to apply energy storage device. Abstract : Recently, carbon nanomaterials are attractive for various applications owing to the benefits derived from their high electrical conductivity, chemical stability and large surface to volume ratio. However, the fabrication process of carbon nanomaterials is complicated and exhibits low productivity. Here we report the facile one-pot synthesis of highly porous 1D carbon nanotubes based on three-layered polymer nanofibers by using a dual-nozzle co-electrospinning technique to apply to an energy storage device. Specific capacitance ( C G ) of the porous carbon nanotube-based electrode is 401 F g −1, which is larger than that of the other carbon nanomaterials. Furthermore, the porous carbon nanotube exhibits excellent rate capability and cycle stability due to micro-/mesopores in the carbon structure enhancing the active surface area between carbon and the ions of the electrolytes. This unique fabrication technique is an effective approach for forming large scale highly porous carbon nanomaterials for diverse electrochemical applications.